Conformational searching of transition metal compounds - Bartol, Jessica; Comba, Peter (Journal of computational chemistry, 1999)
To date, no conformational search of inorganic complexes has been reported that searches for all the conformations and configurations available to the complex. This is due to the various coordination geometries that transition metal ions can adopt and the difficulties in conducting conformational searches with systems that have connected ring systems, such as the ones formed when a metal ion binds a multidentate ligand. Using three test complexes {[Co(dien)2]3+, [Co(dien)(dpt)]3+, and [Co(hexamethylcyclam)(Cl) 2+} the ability of the random kick (Cartesian stochastic Monte Carlo search) method and the Monte Carlo dihedral and positional method to find all conformations and geometric isomers was tested (dien, diethylenetriamine; dpt, di(3-aminopropyl)amine; hexamethylcyclam: tet-a, meso-5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane; tet-b, racemic-5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane). Both methods are significant improvements on the current method by which all possible isomers are entered graphically and minimized individually. The major difficulty that was encountered was how to differentiate between the large number of similar conformations found.